1983
DOI: 10.1139/v83-107
|View full text |Cite
|
Sign up to set email alerts
|

I. Order–disorder transitions and solid state reaction kinetics in Na2SO4–K2SO4 system

Abstract: M. SUNITHA KUMARI and ETALO A. SECCO. Can. J . Chcm. 61, 594 (1983) The physicochemical aspects of the order-disorder phase transitions occurring in the Na2SOI-K2S0, system were investigated by thermal analyses, infrared absorption, and X-ray diffraction methods.Kinetic and structural studies on the compounds KNaSO, and K,Na(S0,)2 are reported in more detail.M. SUNITHA KUMARI et ETALO A. SECCO. Can. J . Chcm. 61, 594 (1983).Faisant appel i I'analyse thermique, a I'absorption infrarougc et i la diffraction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…(4). As one can see [16], the further increase of x results in disappearance of the second high temperature phase besides the increase in the value of specific heat Cp at the first high temperature phase the same neutron fluence. …”
Section: Resultsmentioning
confidence: 88%
“…(4). As one can see [16], the further increase of x results in disappearance of the second high temperature phase besides the increase in the value of specific heat Cp at the first high temperature phase the same neutron fluence. …”
Section: Resultsmentioning
confidence: 88%
“…A high-temperature solid solution with a hexagonal crystal structure also exists, and the intermediate phase, glaserite, K 3 Na(SO 4 ) 2 , shows considerable non-stoichiometry at temperatures above room temperature [27,28,[39][40][41][42]. Only the hexagonal phase shows solid solution over the whole compositional range of (Na 2 SO 4 + K 2 SO 4 ).…”
Section: Thermodynamic Model For the Solid Solutionsmentioning
confidence: 99%
“…
A characteristic first-order phase transition of a solidsolid transformation in NaKSO4 crystals was observed using thermal analysis, infrared and X-ray diffraction techniques [1]. Previous studies of thermal properties of NaKSO4 crystals showed an anomaly in the temperature dependence of specific heat (Cp), linear thermal expansion coefficient, ~j, and heat transition, AQ, at 453 K [2].
…”
mentioning
confidence: 99%